ASSESSMENT OF THE BIOACCUMULATION OF MICROPLASTICS IN THE BLACK SEA MUSSEL Mytilus galloprovincialis L., 1819 - Sevginar Ibryamova; Stephany Toschkova; Darina Ch. Bachvarova; Aysel Lyatif; Elitca Stanachkova; Radoslav Ivanov; Nikolay Natchev; Tsveteslava Ignatova-Ivanova (Peytchinski Publishing, 2022)
The accumulation of microplastics in the world oceans is one of the main global problems of the modern world. The Black Sea is the main source of seafood for people from several countries, including Bulgaria. The pollution of the Black sea is a result of various factors, especially anthropogenic. The aim of this study was to determine the presence and accumulation of microplastics in the Black Sea mussel Mytilus galloprovincialis L., 1819, harvested from different locations along the northern Bulgarian Black Sea coast. Within each microplastic morphological group, three size classes were recognized: 100-200 μm, 25-100 μm, and ≤ 25 μm. Microplastics were found in the soft tissues of all studied specimens but in a different ratio of pellets, fibers and fragments. Generally, the pellets were the most often registered particles, followed by irregularly-shaped fragments, whereas fibers were less numerous. The dominant part of the isolated plastics are made of polyethylene (PE), and polyethylene terephthalate (PET). Our results pointed out serious pollution with plastic particles in the Bulgarian Black Sea aquatory, which in the future may seriously affect the health of the mussel population and also human health.